Nonalcoholic fatty liver disease with cirrhosis increases familial risk for advanced fibrosis - Caussy, Cyrielle (J Clin Invest, 2017)
BACKGROUND. The risk of advanced fibrosis in first-degree relatives of patients with nonalcoholic fatty liver disease and cirrhosis (NAFLD-cirrhosis) is unknown and needs to be systematically quantified. We aimed to prospectively assess the risk of advanced fibrosis in first-degree relatives of probands with NAFLD-cirrhosis. METHODS. This is a cross-sectional analysis of a prospective cohort of 26 probands with NAFLD-cirrhosis and 39 first-degree relatives. The control population included 69 community-dwelling twin, sib-sib, or parent-offspring pairs (n = 138), comprising 69 individuals randomly ascertained to be without evidence of NAFLD and 69 of their first-degree relatives. The primary outcome was presence of advanced fibrosis (stage 3 or 4 fibrosis). NAFLD was assessed clinically and quantified by MRI proton density fat fraction (MRI-PDFF). Advanced fibrosis was diagnosed by liver stiffness greater than 3.63 kPa using magnetic resonance elastography (MRE). RESULTS. The prevalence of advanced fibrosis in first-degree relatives of probands with NAFLD-cirrhosis was significantly higher than that in the control population (17.9% vs. 1.4%, P = 0.0032). Compared with controls, the odds of advanced fibrosis among the first-degree relatives of probands with NAFLD-cirrhosis were odds ratio 14.9 (95% CI, 1.8–126.0, P = 0.0133). Even after multivariable adjustment by age, sex, Hispanic ethnicity, BMI, and diabetes status, the risk of advanced fibrosis remained both statistically and clinically significant (multivariable-adjusted odds ratio 12.5; 95% CI, 1.1–146.1, P = 0.0438). CONCLUSION. Using a well-phenotyped familial cohort, we demonstrated that first-degree relatives of probands with NAFLD-cirrhosis have a 12 times higher risk of advanced fibrosis. Advanced fibrosis screening may be considered in first-degree relatives of NAFLD-cirrhosis patients. TRIAL REGISTRATION. UCSD IRB: 140084. FUNDING. National Institute of Diabetes and Digestive and Kidney Diseases and National Institute of Environmental Health Sciences, NIH.